Systemic Immune-Inflammation Index and Depressive Symptoms in US Adults: Implications for Immunomodulatory Interventions—A Cross-Sectional Study from NHANES 2005–2020 - Fu, Yuhong (Trends in Immunotherapy, 2026)
Inflammatory responses play a crucial role in the pathogenesis of depression. The Systemic Immune Inflammatory Index (SII) is a novel composite inflammatory marker that integrates the counts of neutrophils, lymphocytes, and platelets. However, the relationship between it and depressive symptoms is still not very clear at present. This exploratory study conducted in this article aims to investigate the relationship between SII and other immune inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), and depressive symptoms. This can provide some epidemiological evidence for intervening in mental health through immune regulation. Data from the National Health and Nutrition Examination Survey (NHANES) 2005–2020, which included 32,683 adults 18 years of age and older, were used in this exploratory cross-sectional analysis. Because this study generated hypotheses, subgroup and sensitivity analyses were carried out, restricted cubic spline (RCS) analysis was utilized to investigate dose-response relationships, and weighted multivariable logistic regression was utilized to evaluate association strength. The highest quartile of SII was significantly associated with elevated depression risk (odds ratio (OR) = 1.23, 95% confidence interval (CI): 1.05–1.44, p for trend = 0.008), with a J-shaped dose-response relationship. The association was stronger among participants with diabetes (OR = 1.56, p for interaction = 0.038). NLR showed a borderline association, while PLR and MLR demonstrated no significant associations. SII was independently and positively associated with depressive symptoms and may serve as a potential biomarker for depression risk stratification, with implications for developing immunomodulatory intervention strategies.